Defining Social Housing: A Discussion on the Suitable Criteria. Issue 2 (3rd April 2019) - Granath Hansson, Anna; Lundgren, Björn
Abstract: The term social housing has been characterized as a "floating signifier", i.e. a term with no agreed-upon meaning. The lack of a definition often leads to misunderstandings, rather than constructive dialogue on the advantages and disadvantages of such a system. The aim of this article is to contribute to clarity by providing a discussion on the potential defining criteria of social housing and suggesting a definition of the concept. Definitions of the term social housing and descriptions of European social housing systems used in the last eight years will be presented and discussed. Five potential defining criteria derived from the literature are evaluated as to their sufficiency and necessity for a definition.